# RD Sharma Class 12 Ex 6.5 Solutions Chapter 6 Determinants

Here we provide RD Sharma Class 12 Ex 6.5 Solutions Chapter 6 Determinants for English medium students, Which will very helpful for every student in their exams. Students can download the RD Sharma Class 12 Ex 6.5 Solutions Chapter 6 Determinants book pdf download. Now you will get step-by-step solutions to each question.

## RD Sharma Class 12 Ex 6.5 Solutions Chapter 6 Determinants

### 5x + 4y – 9z = 0

Solution:

Given:

x + y – 2z = 0

2x + y – 3z =0

5x + 4y – 9z = 0

This system of equations can be expressed in the form of a matrix AX = B

Now find the determinant,

= 1(1 × (-9) – 4 × (-3)) – 1(2 × (-9) – 5 × (-3)) – 2(4 × 2 – 5 × 1)

= 1(-9 + 12) – 1(-18 + 15) – 2(8 – 5)

= 1 × 3 – 1 × (-3) – 2 × 3

= 3 + 3 – 6

= 0

So, D = 0, that means this system of equations has infinite solution.

Now,

Let z = k

⇒ x + y = 2k

And 2x + y = 3k

Now using the Cramer’s rule

x =

x =

x =

x = k

Similarly,

y =

y =

y =

y = k

Therefore,

x = y = z = k.

### 2x + 5y – 2z = 0

Solution:

2x + 3y + 4z = 0

x + y + z = 0

2x + 5y – 2z = 0

This system of equations can be expressed in the form of a matrix AX = B

Find the determinant

= 2(1 × (-2) – 1 × 5) – 3(1 × (-2) – 2 × 1) + 4(1 × 5 – 2 × 1)

= 2(-2 – 5) – 3(-2 – 2) + 4(5 – 2)

= 2 × (-7) – 3 × (-4) + 4 × 3

= -14 + 12 + 12

= -10

Hence, D ≠ 0, so the system of equation has trivial solution.

Therefore, the system of equation has only solution as x = y = z = 0.

### 2x +5y – 2z = 0

Solution:

Given:

3x + y + z = 0

x – 4y + 3z = 0

2x +5y – 2z = 0

This system of equations can be expressed in the form of a matrix AX = B

Find the determinant

= 3(8 – 15) – 1(-2 – 6) + 1(13)

= -21 + 8 + 13

= 0

So, the system has infinite solutions:

Let z = k,

So,

3x + y = -k

x – 4y = -3k

Now,

x =

y =

x =

y =

z = k

and there values satisfy equation 3

Hence, x = -7k, y = 8k, z = 13k

### 2x + λz = 0

Solution:

Finding the determinant

= 3λ3 + 2λ – 8 – 6λ

= 2λ3 – 4λ – 8

Which is satisfied by λ = 2 {for non-trivial solutions λ =2}

Now let z = k

4x – 2y = -3k

x + 2y = -3k

x =

y =

Hence, the solution is x = -k, y = , z = k

### has a non-trivial solution, then prove that ab + bc + ca = abc

Solution:

Finding the determinant

Now for non-trivial solution, D = 0

0 = (a – 1)[(b – 1)(c – 1) – 1]+1[-c + 1 – 1] + [-c + 1 – 1] – [ 1 + b – 1]

0 = (a – 1)[bc – b – c + 1 – 1] – c – b

0 = abc – ab -ac + b + c – c – b

ab + bc + ac = abc

Hence proved

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment in the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share rdsharmasolutions.in to your friends.